High-reliability forming anti-cracking method for FP / QFP device

By improving the pin substrate materials and processes of FP/QFP devices and optimizing brazing and electroplating processes, the problems of pin grain boundaries are solved, and the reliability and crack resistance of the device are significantly improved.

CN119742235APending Publication Date: 2025-04-01CHINA ACADEMY OF SPACE TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411842794.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The pins of FP/QFP devices are prone to grain boundary weakening and cracking after soldering, resulting in reduced device reliability.

Method used

By improving the composition and process design of the pin substrate material, optimizing the brazing and electroplating processes, improving the pin's crack resistance. Specific measures include optimizing the composition of 4J42 and 4J29 alloys, adopting a dual vacuum smelting process, controlling the content of impurity elements, performing double-sided etching and annealing treatment, controlling the diffusion of AgCu solder, and optimizing the nickel plating thickness and annealing process.

Benefits of technology

It significantly improves the crack resistance of FP/QFP device pins, enhances the reliability and stability of the device, solves the problem of pin cracking, and improves the versatility and quality of the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742235A_ABST
    Figure CN119742235A_ABST
Patent Text Reader

Abstract

A high-reliability forming anti-cracking method of an FP / QFP device belongs to the technical field of precise instruments, and comprises the following steps: performing failure analysis on a device with cracked pins to find defects; the failure analysis method comprises the steps of appearance inspection, X-ray inspection, metallographic sectioning, surface treatment, metallographic erosion, scanning electron microscope observation, energy spectrum analysis and electron back scattering diffraction (EBSD) grain analysis. Improvements are carried out aiming at existing defects, and comprise improvement aiming at a traditional tube shell pin base material of the FP / QFP device, improvement aiming at a lead brazing and electroplating process in tube shell production, and improvement aiming at a pin forming and electric fitting process of the FP / QFP device. Components and process design of a traditional base material are improved in the development stage of the pin base material, and the crack resistance of the traditional material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-reliability forming and crack-resistance method for FP / QFP devices, belonging to the technical field of precision instruments. Background Art

[0002] At present, the metal ceramic shell pins of FP / QFP devices are mostly welded to the metallization of the welding area of ​​the aluminum oxide ceramic body through silver-copper solder. The commonly used materials for the pins are 4J29 and 4J42 alloys. 4J29 alloy is also called Kovar alloy. As a kind of expansion alloy, it has a relatively low expansion coefficient. Due to its magnetostrictive effect, it has a constant thermal expansion coefficient in the temperature range of 20 to 450°C. It can be matched and sealed with glass and ceramics. It has considerable advantages in processability and weldability, so it is widely used in the field of electronic packaging; 4J42 alloy belongs to the expansion alloy among precision alloys, with a nickel content of about 42%, and the rest is mainly iron. It has a stable low expansion coefficient (the average expansion coefficient at room temperature is 1.6×10-6 / °C), and is widely used in aerospace, precision instruments, and electronics industries. Ag series solder is the type of solder with the longest history of use and the most widespread application. In particular, Ag-Cu eutectic (Ag72-Cu28) solder is the most widely used solder in vacuum devices. It has a low melting point, no crystallization interval, good fluidity, and the formed weld has good thermal conductivity and electrical conductivity. Therefore, in the manufacture of vacuum devices, its usage accounts for more than 80% of the total solder. FP / QFP devices are widely used in various parts of electronic equipment, with large usage, and are mostly devices that realize basic functions such as triggers and inverters.

[0003] During the production process of FP / QFP metal ceramic package shell, AgCu solder is used to weld the pins of 4J29, 4J42 and other base alloys to the ceramic tube seat. Silver-copper solder is easily corrosive to 4J29 and 4J42 alloy materials, and it is easy to flow on the lead frame after welding, causing AgCu solder to penetrate along the grain boundary of the base alloy, causing grain boundary weakening. The grain boundary weakening of the lead base material leads to irreparable cracking at the bend after forming, which seriously affects the reliability of the device. In recent years, many FP / QFP device pin cracking problems have occurred in succession on multiple models of general-purpose stand-alone machines after electrical installation, resulting in failure cases with major impacts such as abnormal device electrical connectivity and batch replacement.

[0004] Different combinations of lap length, device stand height, and shoulder width in the pin forming parameters have an important impact on the quality of the device after welding. Due to the inconsistency of silver and copper penetration in different devices, the forming parameter indicators of each unit are inconsistent, the forming level is uneven, and there is a lack of universal forming regulations; at the same time, changes in forming and electrical parameters will lead to a series of changes in pad size, PCB wiring board, etc., and the versatility will deteriorate. Therefore, it is urgent to carry out technical research on improving the crack resistance of FP / QFP device pin forming, form new requirements for FP / QFP device high-reliability pin optimization forming electrical process, and provide targeted guidance for users to form electrical equipment.

[0005] FP / QFP metal-ceramic packaged devices are prone to tiny cracks at the first bend of the leads after lead forming or electrical assembly. This is a common quality problem faced by all device manufacturers and has occurred many times during the use of the model. Currently, there has been no in-depth research on the mechanism and laws of the failure, and there is a lack of systematic solutions, which poses a high risk for subsequent use. Summary of the invention

[0006] The technical problem solved by the present invention is: to overcome the deficiencies of the prior art, to provide a high-reliability forming and crack-resistant method for FP / QFP devices, to improve the composition and process design of traditional substrates during the development stage of pin substrate materials, and to enhance the crack-resistant ability of traditional materials.

[0007] The technical solution of the present invention is: a high-reliability forming and crack-resistant method for FP / QFP devices, comprising:

[0008] Failure analysis is performed on the device with cracked pins to find defects; the failure analysis method includes appearance inspection, X-ray inspection, metallographic sectioning, surface treatment, metallographic etching, scanning electron microscope observation, energy spectrum analysis, and electron backscatter diffraction EBSD grain analysis;

[0009] Improvements are made to address existing defects, including: improvements to the base material of traditional tube shell pins of FP / QFP devices, improvements to the lead brazing and electroplating processes in tube shell production, and improvements to the pin forming and electrical assembly processes of FP / QFP devices.

[0010] Furthermore, the improvement of the conventional tube shell pin substrate material for FP / QFP devices includes:

[0011] Optimize the composition of national standard 4J42 alloy and 4J29 alloy;

[0012] Industrial pure iron is selected, and a double vacuum melting process of a vacuum induction furnace and vacuum consumable arc melting is adopted to control the content of impurity elements in nickel and cobalt metals. Among the impurity elements, the carbon content of the pin substrates 4J42 and 4J29 is not more than 0.03 and 0.02 respectively, the phosphorus content is not more than 0.02 and 0.02 respectively, and the sulfur content is not more than 0.003 and 0.003 respectively.

[0013] Furthermore, the optimization of the composition of the national standard 4J42 alloy and 4J29 alloy includes:

[0014] The nickel content is controlled within the required upper limit value. The upper limit value ranges of the nickel content in the lead substrate 4J42 and 4J29 alloys are 41.8~42.5 and 29.0~29.5 respectively.

[0015] Furthermore, the improvement of the preparation process before lead brazing in tube shell production includes:

[0016] Double-sided etching is adopted to reduce the etching speed, set the optimal concentration range, temperature range and etching time of the etching solution, determine the appropriate process parameters for the etching process, and compare the etching depth before and after optimization and the pin fatigue before and after optimization to clarify the improvement effect of the optimized etching depth and the number of fatigue times of the optimized pins; different materials have different parameters, and the actual material shall prevail.

[0017] Furthermore, the improvement of the lead brazing process in the tube shell production includes:

[0018] Annealing the FeNi alloy;

[0019] The flowability of AgCu solder on the lead surface during brazing is controlled to control the amount of brazing solder.

[0020] Furthermore, the annealing treatment includes eliminating machining stress, eliminating work hardening, and making the material structure uniform.

[0021] Furthermore, the improvement of high-reliability lead forming and electrical assembly process for FP / QFP devices includes:

[0022] Through simulation, digital assembly is performed, and the response of the assembly under mechanical and thermal environmental stress is analyzed. The focus parameters are clearly identified, including bending speed, shoulder width, angle, overlap length, stand height, and bending radius. Theoretical analysis and simulation optimization are completed to provide a basis for subsequent targeted improvements.

[0023] After completing the theoretical analysis and simulation optimization, actual targeted assessment tests and evaluations are carried out. During the evaluation, a group control group is set up, and the process parameters are optimized according to the assessment and evaluation results to form an optimization method for the lead forming and electrical assembly processes of FP / QFP devices.

[0024] Furthermore, the improvement of the lead electroplating process in the tube shell production includes:

[0025] Control of nickel plating thickness after brazing; control the thickness of nickel plating layer to be no more than 6μm;

[0026] Annealing after nickel plating of brazed parts;

[0027] By controlling the plating thickness and conducting a comparative test on the annealing of the brazed parts after nickel plating, the relationship with the number of lead fatigue bending times is determined and the optimal result is selected.

[0028] Furthermore, a metallographic corrosion analysis is performed on the device after the environmental assessment test. Different corrosion solutions and corrosion rates are matched according to the materials. A metallographic microscope and SEM are used to observe the depth of the silver-copper solder penetrating into the substrate alloy at the first bend of the improved pin. The effect of the improvement is verified by comparison. The smaller the penetration depth, the better, and less than 2μm is the best.

[0029] The advantages of the present invention compared with the prior art are:

[0030] (1) The present invention improves the overall robustness of the product from two aspects: inherent reliability and reliability in use. The current forming anti-cracking method is aimed at the reliability of product use. The anti-cracking effect of the product is improved by reinforcement and protection, but it is impossible to improve the product performance from the source.

[0031] (2) The present invention starts from the more fundamental improvement of the substrate, with an early intervention stage, and improves from four aspects: chemical composition design, trace element addition, raw material selection, and production process. On the basis of ensuring that the mechanical properties of the material meet the normal application of the product, the material cleanliness and intercrystalline bonding strength of the pin substrate are improved, and the grain size is refined, laying a good foundation for the subsequent pin crack resistance. The improved material formed can be promoted and applied to products with similar needs.

[0032] (3) Based on the improvement of the pin substrate, the present invention focuses on the reliability of the connection between the pin and the ceramic body. By designing a series of experiments, reasonable and effective brazing and electroplating process methods are clarified to further improve the inherent reliability.

[0033] (4) The high-reliability pin forming and electrical assembly process optimization method for FP / QFP devices formed by the present invention fully considers the mechanical and thermal environment conditions under high-reliability applications. It is refined and optimized based on the team's many years of engineering experience. The formed method is highly practical and has a wide coverage. It is currently leading in China.

[0034] (5) Based on many years of engineering experience accumulation and failure case analysis, combined with unique high-reliability application environment considerations, the present invention can more accurately locate the key factors affecting the quality of the pin's anti-cracking performance, clarify the influencing rules, and effectively guide subsequent improvements. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0036] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0037] In order to better understand the above technical scheme, the technical scheme of the present invention is described in detail below through the accompanying drawings and specific embodiments. It should be understood that the embodiments of the present invention and the specific features in the embodiments are detailed descriptions of the technical scheme of the present invention, rather than limitations on the technical scheme of the present invention. In the absence of conflict, the embodiments of the present invention and the technical features in the embodiments can be combined with each other.

[0038] The following is a further detailed description of a high-reliability forming and crack-resistant method for FP / QFP devices provided by an embodiment of the present invention in conjunction with the accompanying drawings of the specification. The specific implementation method may include:

[0039] Failure analysis is performed on the device with cracked pins to find defects; the failure analysis method includes appearance inspection, X-ray inspection, metallographic sectioning, surface treatment, metallographic etching, scanning electron microscope observation, energy spectrum analysis, and electron backscatter diffraction EBSD grain analysis;

[0040] Improvements are made to address existing defects, including: improvements to the base material of traditional tube shell pins of FP / QFP devices, improvements to the lead brazing and electroplating processes in tube shell production, and improvements to the pin forming and electrical assembly processes of FP / QFP devices.

[0041] Improvements to the traditional tube and pin substrate materials for FP / QFP devices include:

[0042] Optimize the composition of national standard 4J42 alloy and 4J29 alloy;

[0043] Industrial pure iron is selected, and a double vacuum melting process of a vacuum induction furnace and vacuum consumable arc melting is adopted to control the content of impurity elements in nickel and cobalt metals. Among the impurity elements, the carbon content of the pin substrates 4J42 and 4J29 is not more than 0.03 and 0.02 respectively, the phosphorus content is not more than 0.02 and 0.02 respectively, and the sulfur content is not more than 0.003 and 0.003 respectively.

[0044] The composition of the national standard 4J42 alloy and 4J29 alloy is optimized, including:

[0045] The nickel content is controlled within the required upper limit value. The upper limit value ranges of the nickel content in the lead substrate 4J42 and 4J29 alloys are 41.8~42.5 and 29.0~29.5 respectively.

[0046] Improvements to the lead brazing preparation process in tube and shell production include:

[0047] Double-sided etching is adopted to reduce the etching speed, set the optimal concentration range, temperature range and etching time of the etching solution, determine the appropriate process parameters for the etching process, and compare the etching depth before and after optimization and the pin fatigue before and after optimization to clarify the improvement effect of the optimized etching depth and the number of fatigue times of the optimized pins; different materials have different parameters, and the actual material shall prevail.

[0048] Improvements to the lead brazing process in tube and shell production include:

[0049] Annealing the FeNi alloy;

[0050] The flowability of AgCu solder on the lead surface during brazing is controlled to control the amount of brazing solder.

[0051] Annealing treatment includes eliminating machining stress, eliminating work hardening, and making the material structure uniform.

[0052] Improvements to high-reliability lead forming and electrical assembly processes for FP / QFP devices, including:

[0053] Through simulation, digital assembly is performed, and the response of the assembly under mechanical and thermal environmental stress is analyzed. The focus parameters are clearly identified, including bending speed, shoulder width, angle, overlap length, stand height, and bending radius. Theoretical analysis and simulation optimization are completed to provide a basis for subsequent targeted improvements.

[0054] After completing the theoretical analysis and simulation optimization, actual targeted assessment tests and evaluations are carried out. During the evaluation, a group control group is set up, and the process parameters are optimized according to the assessment and evaluation results to form an optimization method for the lead forming and electrical assembly processes of FP / QFP devices.

[0055] Improvements to the lead plating process in tube and shell production include:

[0056] Control of nickel plating thickness after brazing; control the thickness of nickel plating layer to be no more than 6μm;

[0057] Annealing after nickel plating of brazed parts;

[0058] By controlling the plating thickness and conducting a comparative test on the annealing of the brazed parts after nickel plating, the relationship with the number of lead fatigue bending times is determined and the optimal result is selected.

[0059] Metallographic corrosion analysis was performed on the devices after the environmental assessment test. According to the material combination of different corrosion solutions and corrosion rates, a metallographic microscope and SEM were used to observe the depth of silver-copper solder penetrating into the substrate alloy at the first bend of the improved pin. The effect of the improvement was verified by comparison. The smaller the penetration depth, the better, and less than 2μm is the best.

[0060] In the solution provided in the embodiment of the present invention,

[0061] (1) Technical solutions for typical failure modes, mechanisms and research methods of major influencing factors

[0062] The present invention performs failure analysis on devices with cracked pins, and adopts appearance inspection, X-ray inspection, metallographic sectioning, surface treatment, scanning electron microscope observation, energy spectrum analysis, electron backscatter diffraction EBSD grain analysis, etc. to analyze the problem, clarify the actual state of the sample, and facilitate the discovery of existing defects.

[0063] We will continue to explore and summarize, integrate the principles of efficiency, operational safety and cost savings, and ultimately determine a more reasonable failure detection method, conduct more in-depth research on failure modes and failure mechanisms, and clarify failure modes and cause mechanisms.

[0064] (2) Technical solutions for improving the base material of traditional tube shell pins of FP / QFP devices 1) Improvement method

[0065] The effective means are to achieve this through chemical composition design, trace element addition, raw material selection and production process.

[0066] 1) Chemical composition design, trace element design

[0067] The composition of the national standard 4J42 alloy and 4J29 alloy is optimized, and trace elements are added. The specific optimization is as follows:

[0068] a) Through the double vacuum smelting method, the carbon content can be reduced;

[0069] b) Controlling the nickel content above the requirement can slightly improve the corrosion resistance of the alloy strip;

[0070] c) Reduce the S content.

[0071] On the basis of optimizing the composition design, trace amounts of mixed rare earth and other elements are added to obtain more excellent alloy strips in terms of cleanliness, grain size and uniformity.

[0072] Specifically, industrial pure iron is selected, and a double vacuum melting process of a vacuum induction furnace and vacuum consumable arc melting is adopted to control the content of impurity elements in nickel and cobalt metals. The content control requirements of impurity elements C, P, and S in conventional pin substrates 4J42 and 4J29 alloys are reduced from Table 1 to Table 2.

[0073] Table 1 National standard chemical composition

[0074]

[0075]

[0076] Table 2 Chemical composition after optimization

[0077]

[0078] 2) Selection of raw materials

[0079] a) Strictly select high-purity industrial pure iron;

[0080] b) Control the content of impurity elements in nickel and cobalt metals.

[0081] 3) Production process

[0082] The material properties were optimized by using a double vacuum melting process of vacuum induction furnace + vacuum consumable arc melting.

[0083] II) Evaluation Method

[0084] Conduct evaluation research on the optimization of 4J42 and 4J29 alloy performance by trace element addition, analyze material properties of samples with rare earth elements added, and appropriately select from the following commonly used evaluation tests:

[0085] 1) Purity and chemical composition (ICP analysis)

[0086] 2) Thermal expansion coefficient (thermal expansion analyzer)

[0087] 3) Tensile test, morphology fracture analysis (tensile testing machine, scanning electron microscope)

[0088] 4) Hardness test (microhardness tester)

[0089] 5) Metallographic test (metallographic microscope)

[0090] 6) Inclusion analysis (aspex scanning electron microscope)

[0091] 7) Carbon and sulfur content analysis (carbon and sulfur analyzer)

[0092] Conduct in-depth analysis on the test results and form an evaluation method for the improved materials.

[0093] (3) Technical solutions for optimizing lead brazing and electroplating processes in tube and shell production

[0094] 1) Research on pretreatment of metal materials before brazing

[0095] Double-sided etching is adopted, the etching speed is reduced, the optimal concentration range of the etching solution is set, the reasonably controllable temperature range and the appropriate etching time are set, and finally the suitable process parameters of the etching process are determined. By comparing the etching depth before and after optimization and the pin fatigue comparison results before and after optimization, the improvement effect of the optimized etching depth and the fatigue times of the optimized pins are clarified.

[0096] 2) Study on annealing treatment before brazing

[0097] In order to ensure good bonding between the ceramic shell and the FeNi alloy after brazing, the FeNi alloy needs to be annealed to a) eliminate machining stress, b) eliminate work hardening, and c) make the material structure uniform, refined, stable and consistent.

[0098] 3) Optimize the soldering process and control the flowability of AgCu solder on the pin surface

[0099] The brazing process is optimized and improved mainly from the following aspects, so as to effectively control the fluidity of AgCu solder on the pin surface during brazing.

[0100] a) Study on the amount of solder for different leads and different soldering area sizes

[0101] b) Optimize brazing process curve

[0102] c) Adjust the fixed load

[0103] d) Adjust the spacing of the brazing molds

[0104] 4) Nickel plating of ceramic parts and control of nickel layer thickness

[0105] The uniformity of the thickness of the nickel layer on the ceramic body has a great influence on the welding flow. If the coating thickness is too low, the solder flow will deteriorate. Therefore, a study on the relationship between the lead coating thickness and the number of lead fatigue bending times was conducted.

[0106] 5) Research on annealing process after brazing nickel plating

[0107] Annealing after brazing nickel plating can significantly improve the bending resistance of nickel-plated leads, even close to the level before plating. Experimental research on the effect of lead plating thickness on lead crack resistance was carried out for the improved tube shell, and the effect of annealing process after nickel plating on lead crack resistance was carried out, and an electroplating process optimization method was formed based on the test results.

[0108] (4) Technical solutions for high-reliability lead forming and electrical assembly process optimization methods for FP / QFP devices

[0109] Use simulation to perform digital assembly, analyze the response of the assembly under mechanical and thermal environmental stress, clarify the weak links in forming and electrical assembly, and identify key parameters such as shoulder width, angle, overlap length, stand height, bending radius, etc., to provide a basis for subsequent targeted improvements. After completing theoretical analysis and simulation optimization, conduct actual targeted assessment test evaluation, set up group control groups during evaluation, and further optimize process parameters based on the assessment results to form a high-reliability lead forming and electrical assembly process optimization method for FP / QFP devices.

[0110] Improvements to the lead plating process in tube and shell production include:

[0111] Control of nickel plating thickness after brazing; control the thickness of nickel plating layer to be no more than 6μm;

[0112] After nickel plating, the brazed parts are annealed. During annealing, the high temperature drives the fine particles to remelt, contact and grow. Recrystallization makes the Ni layer dense and the surface smooth. Annealing reduces the internal stress of the nickel plating layer, softens the plating layer, and densifies the nickel plating layer, enhancing the bonding strength between the plating layer and the substrate. It also helps to eliminate the hydrogen ions introduced by the electroplating process, avoid the hydrogen embrittlement problem of the FeNi alloy lead, improve the bending resistance, corrosion resistance and silver-copper barrier of the nickel plating layer, and significantly improve the quality of the shell in terms of lead bending resistance and corrosion resistance.

[0113] By controlling the plating thickness and conducting a comparative test on the annealing of the brazed parts after nickel plating, the relationship with the number of lead fatigue bending times is determined and the optimal result is selected.

[0114] The metallographic corrosion analysis is performed on the device after the environmental assessment test. According to the material combination of different corrosion solutions and corrosion rates, a metallographic microscope and SEM are used to observe the depth of the silver-copper solder penetrating into the substrate alloy at the first bend of the improved pin, and the effect of the improvement is verified by comparison. The smaller the penetration depth, the better, and less than 2μm is the best.

[0115] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

[0116] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.

Claims

1. A high-reliability forming and crack-resistant method for FP / QFP devices, characterized in that: include: Failure analysis of the device with cracked pins revealed defects; The failure analysis method includes appearance inspection, X-ray inspection, metallographic sectioning, surface treatment, metallographic etching, scanning electron microscope observation, energy spectrum analysis, and electron backscatter diffraction EBSD grain analysis; Improvements are made to address existing defects, including: improvements to the base material of traditional tube shell pins of FP / QFP devices, improvements to the lead brazing and electroplating processes in tube shell production, and improvements to the pin forming and electrical assembly processes of FP / QFP devices.

2. A high-reliability forming and crack-resistant method for FP / QFP devices according to claim 1, characterized in that: The improvement of the conventional tube shell pin substrate material for FP / QFP devices includes: Optimize the composition of national standard 4J42 alloy and 4J29 alloy; Industrial pure iron is selected, and a double vacuum melting process of a vacuum induction furnace and vacuum consumable arc melting is adopted to control the content of impurity elements in nickel and cobalt metals. Among the impurity elements, the carbon content of the pin substrates 4J42 and 4J29 is not more than 0.03 and 0.02 respectively, the phosphorus content is not more than 0.02 and 0.02 respectively, and the sulfur content is not more than 0.003 and 0.003 respectively.

3. A high-reliability forming and crack-resistant method for FP / QFP devices according to claim 2, characterized in that: The optimization of the composition of the national standard 4J42 alloy and 4J29 alloy includes: The nickel content is controlled within the required upper limit value. The upper limit value ranges of the nickel content in the lead substrate 4J42 and 4J29 alloys are 41.8~42.5 and 29.0~29.5 respectively.

4. A high-reliability forming and crack-resistant method for FP / QFP devices according to claim 1, characterized in that: The improvement of the preparation process before lead brazing in tube shell production includes: Double-sided etching is adopted to reduce the etching speed, set the optimal concentration range, temperature range and etching time of the etching solution, determine the appropriate process parameters for the etching process, and compare the etching depth before and after optimization and the pin fatigue before and after optimization to clarify the improvement effect of the optimized etching depth and the number of fatigue times of the optimized pins; different materials have different parameters, and the actual material shall prevail.

5. A high-reliability forming and crack-resistant method for FP / QFP devices according to claim 1, characterized in that: The improvement of the lead brazing process in the tube shell production includes: Annealing the FeNi alloy; The flowability of AgCu solder on the lead surface during brazing is controlled to control the amount of brazing solder.

6. A high-reliability forming and crack-resistant method for FP / QFP devices according to claim 5, characterized in that: The annealing treatment includes eliminating machining stress, eliminating work hardening, and making the material structure uniform.

7. A high-reliability forming and crack-resistant method for FP / QFP devices according to claim 1, characterized in that: The improvement of high-reliability lead forming and electrical assembly process for FP / QFP devices includes: Through simulation, digital assembly is performed, and the response of the assembly under mechanical and thermal environmental stress is analyzed. The focus parameters are clearly identified, including bending speed, shoulder width, angle, overlap length, stand height, and bending radius. Theoretical analysis and simulation optimization are completed to provide a basis for subsequent targeted improvements. After completing the theoretical analysis and simulation optimization, actual targeted assessment tests and evaluations are carried out. During the evaluation, a group control group is set up, and the process parameters are optimized according to the assessment and evaluation results to form an optimization method for the lead forming and electrical assembly processes of FP / QFP devices.

8. A high-reliability forming and crack-resistant method for FP / QFP devices according to claim 1, characterized in that: The improvement of lead electroplating process in tube shell production includes: Control of nickel plating thickness after brazing; control the thickness of nickel plating layer to be no more than 6μm; Annealing after nickel plating of brazed parts; By controlling the plating thickness and conducting a comparative test on the annealing of the brazed parts after nickel plating, the relationship with the number of lead fatigue bending times is determined and the optimal result is selected.

9. A high-reliability forming and crack-resistant method for FP / QFP devices according to claim 1, characterized in that: The metallographic corrosion analysis is performed on the device after the environmental assessment test. According to the material combination of different corrosion solutions and corrosion rates, a metallographic microscope and SEM are used to observe the depth of the silver-copper solder penetrating into the substrate alloy at the first bend of the improved pin, and the effect of the improvement is verified by comparison. The smaller the penetration depth, the better, and less than 2μm is the best.